Guidelines to Improve the Emotional Quotient (EQ) for student in Suan Dusit University - Snguanyat, Ongorn; Srisorn, Wijhittra; Charoensuk, Orn-uma (ASEAN Journal of Education, 2019)
The objective of this paper is to 1) investigate Suan Dusit university (SDU) student’s Emotional Quotient (EQ), and the relationship between the Emotional Quotient (EQ) and the achievement (GPA) of students, 2) to compare the personal status and the Emotional Quotient (EQ), and 3) to provide a recommendation for SDU student’s Emotional Quotient (EQ) development. The collection of data was obtained through qualitative and quantitative methods. The quantitative data were collected from 370 undergraduate students from 7 faculties by using the Emotional Quotient Evaluation Form from the Department of the Mental Health, the Ministry of Public Health and analyzed in terms of t-test, one way ANOVA and Correlation Analysis. In terms of the qualitative data, an in-depth interview method was employed. The results found that; a) SDU students have overall Emotional Quotient (EQ) in normal criterion level and when considered in three main aspects (the goodness, the proficiency, the happiness) shows a normal criterion level. b) The comparison between the personal status and the student’s Emotional Quotient (EQ) found that the students who have differences in personal status (Gender, Faculty, Curriculum, and GPA) shows a statistically significant differences at the level of .05. c) The analysis of the relationship between the EQ level and GPA of students using the Pearson's correlation, found an overall statistically significant positive correlation with the learning achievement of the SDU students which are in a moderate level with a statistical significance level of .05.Moreover, for the Emotional Quotient development of SDU students 2 methods should be implemented; 1) define the University’s policy in EQ development for all students and 2) the faculty should encourage and increase training and activity programs to develop the student in holistic manners, both inside and outside the classroom context.